Correlation Between Sagittal and Transverse Plane Fetal Nuchal Translucency Measurement - Pananya Jomphansa; Suthasinee Metaneedol; Sinart Prommas; Buppa Smanchat; Kornkarn Bhamarapravatana; Komsun Suwannarurk (Siriraj Medical Journal)
Objective: This study aimed to evaluate and compare nuchal translucency (NT) measurement between sagittal and transverse planes for aneuploidy screening.